Assessing the employees’ awareness towards the Total Quality Management (TQM) at Inland Revenue Board Of Malaysia (IRBM), Johor Bahru branch / Nik Noor Afizah Azlan, Nurmuslimah Kamilah Abdullah and Norudin Mansor - Azlan, Nik Noor Afizah; Abdullah, Nurmuslimah Kamilah; Mansor, Norudin (2013)
Total Quality Management (TQM) is a wide, broad, continuous improvement initiative that many organisations have joined the growth of this phenomenon in order to drive their business into sustainable profitability. Therefore, this study examined the employees’ awareness towards TQM at IRBMJB. The objectives of this research are to identify the most relevant factors that contribute to the employees’ awareness towards the TQM and to find the relationship between employees’ awareness and independent variables (Top management commitment and support, employee involvement, and training and education). In assessing the goodness of measures, the factor and reliability analyses were conducted. The factor analysis was revised for three times in order to make sure that there was no item scored for loading less than 0.5. The Cronbach’s Alpha for each concept was between 0.930 - 0.965. Cronbach’s Alpha that was larger than 0.60 indicated that the items measured the intended concepts. The descriptive analysis (frequency distribution) was conducted in reporting the demographic information. The dichotomous scale was used to elicit the yes-and-no answer for the question: “Do you understand about Total Quality Management (TQM) that has been practised by the organisation?” There were 249 employees or 75.5% of the respondents declared that they were aware about TQM which practised by the organisation. The hypothesis testing was conducted by using Pearson Bivariate Correlation. The findings showed that the independent variables which were top management commitment and support, employees’ involvement, and training and education had a strong and significant relationship with employees’ awareness of TQM. As the extension of these results, the multiple regression analysis was conducted. Blending all the three independent variables in explaining the employees’ awareness formed 71.9% of a contributing factor. However, when we went in depth for each independent variable, only two variables would significantly contribute to the employees’ awareness of TQM which were employees’ involvement, and training and education. Thus, the study proved that employees’ involvement, and training and education would influence the employees’ awareness of TQM. To conclude, the organisation should try to focus on top management commitment and support, employee involvement, and training and education in assessing the implementation of TQM in the future since they were associated variables that would influence the awareness of TQM.